Implementation of School Financial Management Function - Yonoriadi; Wahyu Syahrizal; Maimun (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
This study aims to investigate the execution of financial management functions at SMA Negeri 1 Siantar Narumonda, encompassing planning, execution, record-keeping, and oversight of school finances. Employing a qualitative approach with a case study method, data collection is conducted through observation, in-depth interviews, and document analysis. The findings reveal a strong dedication by SMA Negeri 1 Siantar Narumonda towards adopting sound and transparent financial management practices. Financial planning involves various stakeholders in formulating the School Revenue and Expenditure Budget Plan (RAPBS) and the School Activity and Budget Plan (RKAS). The distribution of funds is directed by the RKAS to support the school's operational endeavors. Detailed and systematic financial record-keeping is managed by the school treasurer through ledger books. Periodic financial reports are generated to ensure transparency and answerability. Financial oversight is executed progressively, involving the principal, treasurer, school committee, and the Education Office. External financial audits are conducted regularly to assess the fairness of financial reports and adherence to regulations. This study offers a comprehensive overview of the execution of financial management functions at SMA Negeri 1 Siantar Narumonda and highlights challenges and prospects for enhancing financial management practices in the future.